Implementation of the Recitation Method to Improve Students' High-Order Thinking Skills (HOTS) in Fiqh at MTs At-Taufiqiyah Bluto, Sumenep 2024 - Desri Ani Anggita; Achmad Maulidi (Penerbit Hellow Pustaka, 2026)
The recitation method is a learning strategy that assigns students to study the material independently outside the classroom and present the results in the classroom. This study aims to analyze the implementation of the recitation method in improving students' high order thinking skills in fiqh subjects. Based on the research context, the current era of global competition requires quality learning to provide facilities for students in developing skills, abilities and abilities as capital to face challenges in global life, so the problems raised in this study are 1. How is the implementation of the recitation method in improving students' high order thinking skills in fiqh subjects at MTs At-Taufiqiyah 2. What are the supporting and inhibiting factors in improving students' high order thinking skills in fiqh subjects at MTs At-Taufiqiyah. To find out this problem, the study used a qualitative field approach with data collection techniques through observation, interviews, and documentation. The results of the study show that the effective application of the recitation method is able to encourage students to think critically, analytically, and creatively. In fiqh subjects, students not only memorize concepts, but are also able to understand, analyze, and apply fiqh laws in everyday life. Obstacles encountered included a lack of student preparedness and varying learning abilities, but these could be overcome with intensive guidance and targeted task management. In this study, researchers concluded that the recitation method made a positive contribution to improving students' HOTS, particularly in the analysis, evaluation, and creativity aspects.